Differentiation of malignant and benign breast lesions with diffusion-weighted imaging: What is the optimum apparent diffusion coefficient value? - Lerdwatanakiet, Chawisa; Prueksadee, Jenjeera (The ASEAN Journal of Radiology, 2025)
Background and objective: To determine the optimum apparent diffusion coefficient (ADC) value in differentiating benign from malignant breast lesions. Materials and Methods: The study is a retrospective review of the patients who underwent breast magnetic resonance imaging (MRI) at King Chulalongkorn Memorial Hospital between January 2017 and May 2020. ADC values were measured by placement of region of interest (ROI) within the breast lesions using Philips DynaCAD breast analysis system and comparing it with histopathological diagnosis. A receiver-operating-characteristics (ROC) analysis was plotted and the area under the curve (AUC) was evaluated to find the ideal ADC value in the differentiation of benign and malignant breast lesions. Results: Two hundred and ten lesions in 163 female patients were included in the present study. One hundred twenty-six lesions (60%) were malignant and eighty-four lesions (40%) were benign. The mean ADC values of malignancy (0.913x10-3 mm2/s) were statistically lower than that of benign lesions (1.080x10-3 mm2/s) (mean difference 0.169x10-3 mm2/s, P < 0.001). According to the ROC analysis, the optimum cut-off ADC value of 0.991x10-3 mm2/s was an excellent predictor for differentiated benign and malignant breast lesions (AUC = 0.835, sensitivity 78.6%, specificity 82.5%, accuracy 81%, PPV 85.3% and NPV 75%). Conclusion: Diffusion-weighted imaging (DWI) was an effective MRI sequence to assess breast cancer by using ADC value as a key parameter in addition to other important imaging findings from MRI. The present study showed the mean ADC value of malignancy was statistically significantly lower than that of benign lesions. The cut-off ADC value of 0.991x10-3 mm2/s had good specificity, accuracy, and PPV to differentiate benign from malignant breast lesions.